ACADEMIC TUTORING AS A NEW TREND AND APPROACH IN INDIVIDUAL SUSTAINABILITY EDUCATION - Grażyna SIPIŃSKA; Beata SADOWSKA (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice, 2022)
The natural environment is the foundation of the functioning of the economies and the societies, while, in turn, the society is the bedrock of the economies. "Growth" and "development", "information and knowledge" are now important categories of sustainable development. The goals of sustainable development of individuals must be considered in three dimensions: economic, ecological and social. All these dimensions are based on knowledge, which implies the decisions of individuals. Knowledge is transmitted from an early age, and education is created at different levels, by different teachers, educators, experts. The idea of academic tutoring is based on an individualized approach to the student, where the professor-tutor is both a teacher and a kind of academic guide, and the student is an active partner in the educational situation. The purpose of this study is to assess the level of use of academic tutoring at Polish universities and to present the possibility of applying this method in the sustainable development of the individual. The research problem was defined in the form of research questions. The key research questions that were sought to be answered were formulated as follows: 1. Do Polish public and private education use the modern method of education that is tutoring? 2. From what sources should academic tutoring (tutor's salary) be funded? 3. What tools can a tutor use to work with a student? The following research methods were used: critical analysis of the literature, case study, survey method, induction and synthesis method, graphical data presentation technique.